Dotações hídricas e cobertura morta na cultura da mamona em neossolo flúvico no semiárido pernambucano - SILVA, Júlio José do Nascimento (2012)
The objective of this study was to evaluate the influence of different irrigation levels in the presence and absence of mulch on soil moisture dynamics in castor bean (Ricinus Comunnis L.) BRS Energy cultivation in communal farming. The experimental design was completely randomized in factorial scheme (4x2) x3, with four primary treatments, which are the irrigation based on crop evapotranspiration (ETc), L1 = 60% ETc, L2 = 80% ETc; 100% ETc = L3, L4 = 120% ETc, and two secondary treatments, is the absence and presence of mulch on density equal to 12 ton ha-1 and three replicates. Altogether 27 measurements were taken along the crop cycle. The mulch kept the soil moisture above field capacity. The increase in humidity due to the presence of mulch was 23.8% and 26% in the 0-20 cm and 20-40 cm layers, respectively, compared to its absence. Irrigation allowed moisture in both covering systems to present optimal levels, above the field capacity moisture and far below saturation. Furthermore, it was also perfomed growth analysis. The experimental design was a completely randomized in a factorial scheme (4x2) x4. Eight measurements were performed in the following periods: 15, 30, 45, 60, 75, 90, 105 and 120 days after germination (DAG) and evaluated three plants per plot. Analyses of non-destructive growth, stem diameter (AD), plant height (PH) and Leaf Area Index (LAI). From the measured data of AP, DC, and IAF, we calculated the absolute growth rate (AGR) and relative growth rate (RGR) for each variable respectively. All growth variables showed significant differences along the crop cycle mainly to the presence of cover, except absolute and relative growth rates of DC. The effects of irrigation levels were only significant for plant height (PH) and the Leaf Area Index (LAI). Finally, the crop yield components of castor bean (Ricinus Comunnis L.) were evaluated. The experimental design was same as above. It was performed a single harvest at 120 days after germination (DAG), and sampled three plants per plot. Analyses of the number of racemes per plant (NRP), length of racemes (CR) in centimeters (cm), productivity of fruits (PF) in kilograms per hectare (kg/ha), yield of berries (PG) in kilograms per hectare (kg/ha), mass of 100 seeds (M100) in grams (g) and water use efficiency (EUA) in kilograms of berries per cubic meter (kg/m³) have been performed. All variables except the M100 showed a significant difference to the adopted treatment. The NRP, the PC and the EUA responded significantly to the presence of ground cover, as the CR, the PF and PB responded significantly to the effects of individual irrigation depths and the soil cover. The irrigation depth of 679.77 mm corresponding to 100% of ETc was the best choise allowing an average yield of 2461.4 kg ha-1 of berries for the crop.